(3LGeY GdJUGfja GdQTjOjIs - (3aVd Gddg Hf CHj GdNjQ Hf Ydj CHh GdaVd GdgePGfj , QTjO GdOhdI, Ch QTjO GdOjf,J (B716 (3g` s
(3ChdgG (B:s
(3Ef gPg JPcQg aef TGF GJNP Edi QHg SHjdG s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B74s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B104 s
Keywords: (3GdJGQjNs